"No One Wants to Believe It": Manifestations of White Privilege in a STEM-Focused College. (3rd April 2019) - Grindstaff, Kelly; Mascarenhas, Michael
Abstract : The lagging behind of underrepresented minority (URM) students in higher education, and particularly in the STEM fields, is well documented. In this paper we draw on critical race theory in education to frame and present counter-narratives of URM students in STEM fields, to explicate the function of the interactions that occur between these students and their (mostly White) instructors and peers. Focus group interviews with URM students (and staff) at a STEM focused college identify three ways in which White privilege is enacted through these interactions: in group projects; in cheating accusations; and in the grading process. Our participants illuminate particular manifestations of White privilege in STEM classrooms and on campus, and we place these within the context of "colorblind" changes in higher education in the U.S.